Converting variables between non-hierarchical regions: The case of Austrian municipalities and ZIP-code areas - Dieter Pennerstorfer (Johannes Kepler University of Linz, Department of Economics, 2021)
This report provides a method to convert variables between two non-hierarchical regional levels of aggregation. This approach is applied to municipalities and ZIP-code areas in Austria for the period between 2012 and 2020. Based on detailed information on the spatial distribution of the population at the 250 m grid-cell level and on the spatial extent of both municipalities and ZIP-code areas, I calculate weights to convert variables from one regional entity to the other. This report also provides the data necessary for this data conversion.
Keywords: 330